Prevalence and incidence of postpartum depression among healthy mothers: A systematic review and meta-analysis - Shorey, Shefaly; Chee, Cornelia Yin Ing; Ng, Esperanza Debby; Chan, Yiong Huak; Tam, Wilson Wai San; Chong, Yap Seng (Journal of psychiatric research, 2018)
This review aims to examine the prevalence and incidence of postpartum depression among healthy mothers without prior history of depression including postpartum depression and who gave birth to healthy full-term infants. A systematic search of ClinicalTrials.gov, CINAHL, EMBASE, PsycINFO, and PubMed was performed for English articles from the inception of the database to November 2017, as well as a manual search of the reference lists of the included articles, and an expert panel was consulted. Across 15,895 articles, 58 articles (N = 37,294 women) were included in the review. The incidence of postpartum depression was 12% [95% CI 0.04–0.20] while the overall prevalence of depression was 17% [95% CI 0.15–0.20] among healthy mothers without a prior history of depression. Prevalence was similar regardless of the type of diagnostic tool used; however, there were statistical differences in the prevalence between different geographical regions, with the Middle-East having the highest prevalence (26%, 95% CI 0.13–0.39) and Europe having the lowest (8%, 95% CI 0.05–0.11). There was no statistical difference in prevalence between different screening time points, but an increasing prevalence was observed beyond six months postpartum. Intervention studies often neglect healthy mothers. This review reports a similar prevalence rate of postpartum depression among mothers without history of depression when compared to mothers with history of depression. Thus, future studies should place equal emphasis on this neglected group of mothers so that targeted interventions and follow-ups can be introduced at appropriate time points. •Postpartum depression prevalence of 17% amongst healthy mothers.•Highest prevalence in Middle East and Asia compared to Western countries.•Increasing prevalence in time point assessments beyond three months.•No difference in prevalence through self-reports or clinical interviews.